2019
DOI: 10.1371/journal.pone.0218289
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric impact of oil prices on stock returns in Shanghai stock exchange: Evidence from asymmetric ARDL model

Abstract: This study scrutinized the asymmetric impact of oil prices on stock returns in Shanghai stock exchange with data (January 2000 to December 2018) by using asymmetric ARDL model. The examined results of asymmetric autoregressive distributed lag model indicate that cointegration exists between the oil prices and the stock returns. Results of asymmetric autoregressive distributed lag model confirm that both in the long run and the short run increase in oil prices have a negative impact on the stock returns of Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 58 publications
1
21
1
Order By: Relevance
“…Their short-run results are not statistically significant. Khan et al (2019) also find a statistically significant negative effect of oil price increases on Shanghai Stock Exchange and positive effect of oil price decreases in the long-run and negative effect has a higher coefficient in terms of absolute value. According to their results, in the short-run the positive effect of oil price on stock prices is not statistically significant but the coefficient is statistically significant and positive for the reverse case.…”
Section: Discussionmentioning
confidence: 68%
“…Their short-run results are not statistically significant. Khan et al (2019) also find a statistically significant negative effect of oil price increases on Shanghai Stock Exchange and positive effect of oil price decreases in the long-run and negative effect has a higher coefficient in terms of absolute value. According to their results, in the short-run the positive effect of oil price on stock prices is not statistically significant but the coefficient is statistically significant and positive for the reverse case.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to this, another research found that in the long-run oil price, similar to interest rates and real effective exchange rates, has a negative impact on Malaysia's stock returns, while industrial production has a positive impact [40]. Results of another study using ARDL confirm that both in the long-and short-run there is a negative relationship between Shanghai stock returns and oil price [41].…”
Section: Methodsmentioning
confidence: 87%
“…Authors document the usefulness of crude oil in portfolio diversification but for the short term. Khan et al (2019) study association of oil and Shanghai Stock Exchange (China) for a period 2000-2018 and finds a negative relationship by using ARDL technique. The results of negative association (for the short run) are confirmed by Hsiao et al (2019) after studying the relationship between oil and renewable energy stocks in china for a period 2014-2018.…”
Section: Literature Reviewmentioning
confidence: 99%